The use of the Korean honorific system In the family-themed K-pop (Korean pop) song lyrics - Dwita Rahmah; Didi Sukyadi (Journal of Korean Applied Linguistics, 2023)
Korean society, to this day, generally still applies Confucian principles  in its discourse. Confucian principles in speech are expressed through the use of politeness in language This research conducted to determine how the Korean honorific system is used in the family-themed K-POP (Korean Pop) song lyrics and the factors that influence such use. This research was designed as a qualitative study. The data were collected by using a document analysis technique. Meanwhile, the data analyzed by using a linguistic data analysis technique, with reference to Kang, et al.’s (2005) Korean honorific system theory and Lee’s (2002) theory of social factors that influence the application of the Korean honorific system. This research resulted in 38 Korean honorific system expressions. The most commonly used Korean honorific system type is, namely, the honorific vocabulary. Because songwriters often used vocabulary in the form of honorifics, where the vocabulary was a pronoun to mention the characters in the lyrics of the song. The use of the Korean honorific system was influenced by various factors, including age, social status, intimacy, and context. While the gender factor was not found, this is likely due to the speaker and the addressee having different ages and social status.